PERANCANGAN POSTER TENTANG TATO TRADISIONAL MENTAWAI - Ninik Samukti; Ady Rosa; M. Nasrul Kamal (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
ABSTRACT Mentawai Islands consists of the island of Siberut, Sipora, North Pagai and South Pagai. Many people do not know where the Mentawai Islands. Many of the beauty that can be viewed as exploring unique places. Mentawai Islands, there are several tourist sites such as the Siberut National Park, Dance Sikerei, Turuk Laggai, Tattoos and surfing, is a culture that rarely encountered in other areas, so many tourists who want to see first hand the beauty of Mentawai. Some attractions there are to be promoted and some have not. The authors take an object tattoos that existing media ie local radio advertising, internet, and photos, while I focus on introducing the tattoo through the media poster. Designing a poster aims to show clearly Mentawai tattoo, and can be recognized by the community and beyond. Promotion poster is supported by the media clothes, watches, pins, key chains, x-banner, hats, stickers, calendars and catalogs. Based on the design of the design media campaigns using posters, can be the means / media that is able to seize the attention of the outside community. Kata Kunci: Merancang, Media, Teori SWOT